ECONOMIC EFFICIENCY OF LAND USE BY AGRICULTURAL PRODUCERS IN THE SYSTEM OF THEIR NON–CURRENT ASSETS ANALYSIS: A CASE STUDY OF THE AGRICULTURAL SECTOR OF UKRAINE - Tetiana O. SHMATKOVSKA; Mykola I. DZIAMULYCH; Valentyna M. YAKUBIV; Olha A. MYSHKO; Liudmyla V. STRYZHEUS; Roman D. YAKUBIV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper substantiates that because the soils ploughing level in Ukraine has not changed for a long time, soil depletion is growing every year. As a result of the formed culture tendencies which grow on such lands, every year will lose productivity, and consequently, the efficiency of managing the agricultural enterprises systematically decreases. Cartogram of Ukrainian regions grouping by the average annual rent for the agricultural land use is given. It was found that that in the current business environment in Ukraine, the amount of rent does not depend on the soil fertility level, because in most western, southern and south–eastern regions of Ukraine, where the most fertile soils are concentrated, the level of rent is relatively low. In addition, it should be noted that the agricultural land of public and private ownership renting cost differs significantly from each other, which we found by comparing the data of the relevant cartograms of Ukraine. We systematized the results of the impact factors assessing on the sale of gross output of agricultural enterprises of Ukraine in 2014 – 2018 by analysing the dynamics of the return rate on their fixed assets and the factors that influenced its formation. The results of the factor analysis will make it possible to identify the quantitative impact of factors on the efficiency of non-current assets of agricultural producers, the significant share of which is directly occupied by land resources. The work is systematized the results of assessing the impact of factors on the return on assets of agricultural producers of Ukraine for 2014 - 2018 by identifying the factors that influenced its formation by determining their quantitative impact through factor analysis methods, including the method of elimination. It is substantiated that having significant and quite high–quality reserves of fertile lands, Ukraine is 2–3 times less productive than developed countries, which is evidence of inefficient use of agricultural land by agricultural enterprises of Ukraine. In our opinion, the main task of the state to rationalize and establish the efficient use of land resources in the agricultural sector is to introduce a number of measures to ensure efficient land use.